2011
DOI: 10.26634/jpsy.4.4.1416
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design For Transition: A Single Subject Research Study On The Impact Of UDT On Student Achievement, Engagement And Interest

Abstract: Universal design for transition (UDT) refers to an approach to instructional planning, delivery, and assessment that bridges the gap between teaching academic and functional/transition goals. It builds upon the principals of universal design for learning (UDL) assuring that instructional practices are designed to meet the needs of diverse learners through the use of multiple means of engagement, expression, and representation. UDT assures that instruction includes multiple transition domains, multiple transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This allows educators to meet the needs of a wider range of students through varied and flexible instruction (Meyer et al, 2014). There is empirical support for UDL’s effectiveness with students with and without disabilities, including those with ID from the K–12 through college levels of instruction (e.g., Boothe et al, 2018; Coyne et al, 2017; Scott et al, 2011). In a systematic review of 17 empirically-based UDL studies, Seok et al (2018) found effectiveness in 15 studies, and they concluded that the application of UDL principles was effective for all students with or without disabilities.…”
Section: The Overlap Of Aba and Udlmentioning
confidence: 99%
“…This allows educators to meet the needs of a wider range of students through varied and flexible instruction (Meyer et al, 2014). There is empirical support for UDL’s effectiveness with students with and without disabilities, including those with ID from the K–12 through college levels of instruction (e.g., Boothe et al, 2018; Coyne et al, 2017; Scott et al, 2011). In a systematic review of 17 empirically-based UDL studies, Seok et al (2018) found effectiveness in 15 studies, and they concluded that the application of UDL principles was effective for all students with or without disabilities.…”
Section: The Overlap Of Aba and Udlmentioning
confidence: 99%
“…UDT refers to an approach that bridges the gap between teaching academic and functional/transition goals [28]. UDT combines the concept of barrier-free learning from UDL2 with the transition-based principles as explained by Bruno and Scott (2019) [ 4.…”
Section: Universal Design For Transition (Udt)mentioning
confidence: 99%
“…Compared to the UDL framework, on which UDT was based, the UDT design is simple and intuitive, and it is comprehensible by users with a diversity of language, skill and experience backgrounds (Scott et al, 2011). Perceptible information addresses the degree to which the design communicates needful information in a manner that is unaffected by conditions and sensory abilities.…”
Section: Seven Principles Of Universal Design For Transitionmentioning
confidence: 99%
“…To realize program success, the teachers must fully understand the principles of UDT. The disabilities literature contains extensive background in the areas of teacher preparation, transition planning and professional development for special needs instructors and conclusively calls for more evidence-based research (Fowler et al, 2014;Scott et al, 2011). In the context of Saudi Arabian schools, a study by Aldabas (2015) suggested intensive instructor training and national special education policies.…”
Section: The Role Of Understanding Udt Principles In Improvingmentioning
confidence: 99%
See 1 more Smart Citation